2021
DOI: 10.1101/2021.01.15.426787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of Computerized Tomography (CT) Severity Score for COVID-19 pneumonia with Clinical Outcomes

Abstract: IntroductionVarious CT severity scores have already been described in literature since the start of this pandemic. One pertinent issue with all of the previously described severity scores is their relative challenging calculation and variance in inter-observer agreement. The severity score proposed in our study is relatively simpler, easier to calculate and apart from a trained radiologist, can easily be calculated even by physicians with good inter-observer agreement. Therefore, a rapid CT severity score calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…According to Hilal et al. [ 28 ], patients with a CT severity score of above 7 had a longer hospital stay, lower intensive care supplements need, and decreased mortality rate. The serum CRP levels and CT features had a significant correlation in patients with a score above 7.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hilal et al. [ 28 ], patients with a CT severity score of above 7 had a longer hospital stay, lower intensive care supplements need, and decreased mortality rate. The serum CRP levels and CT features had a significant correlation in patients with a score above 7.…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve (AUC) of CTSS prediction of critical COVID-19 was 0.895 with sensitivity of 79.3% and specificity of 88.1% (Fig. 3 ) when the threshold value is 12 [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 is not likely to be severe, but severe cases of pneumonia often lead to death 2 . Because CT is very useful in determining the severity of the disease, various scoring methods using CT have been used, and it has been found that higher scores are related to the severity of the disease 7,8,[11][12][13][14][15][16][17][18] . Three key points influence the scoring by CT.…”
Section: Discussionmentioning
confidence: 99%
“…The second is how to determine the region of the lung to be scored. Most often, the lungs are read in five lobes (three right and two left lobes) along the anatomical region [7][8][9][11][12][13][14][15][16] . A different way to read the lungs is to divide them into three zones: upper, middle, and lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation